The rough guide to France - Abram, David; Rough Guides (Firm) (London : Rough Guides, 2009)
Presents a travel guide to France, covering culture, history, lodging, restaurants, communications, outdoor activities, shopping, festivals, and attractions, with maps and practical French language tips.
Map on inside cover.
Spine title: France.
Includes bibliographical references (p. 1209-1213), filmography (p. 1199-1208), and index.
Adult
Adult
Keywords: France -- Guidebooks; France -- Guidebooks